Towards opportunistic UAV relaying for smart cities - Hardes, Tobias; Boos, Clemens; Sommer, Christoph (Electronic Communications of the EASST, 2021)
With recent advances in cooperation among mobile computer systems, Unmanned Aerial Vehicles (UAVs) can be expected to be operated in large numbers and become a part of daily life for a variety of use cases. UAVs are already envi- sioned to act as mobile base stations, e.g., for situations with high node densities and strong communication requirements. However, UAVs are typically imagined to be provided specifically for this purpose. In this work, we study the effects of exploiting randomly passing UAVs at an urban intersection for the communication between vehicles on the ground. We show that a UAV, while following its pri- mary mission, can support cooperative driving vehicles in a purely opportunistic fashion by collecting periodic wireless broadcasts from vehicles and propagating all collected information periodically in an aggregated format. Using simulations, we show that such an opportunistic UAV relaying approach can lead to an improvement of approx. 6 percentage points (% points) in terms of perception of other vehicles.